CFD–DEM investigation of the effect of agglomerate–agglomerate collision on dry powder aerosolisation. (February 2016) - Tong, Zhenbo; Zhong, Wenqi; Yu, Aibing; Chan, Hak-Kim; Yang, Runyu
Abstract: This paper investigated the behaviour of agglomerate–agglomerate collision based on a combined computational fluid dynamics (CFD) and discrete element method (DEM) approach, aiming to develop better understanding of the underlying the mechanisms of loose drug agglomerates aerosolisation in DPIs. The collision between two mannitol agglomerates in a T-shape pipe was simulated. The effects of key variables such as agglomerate strength, air flow rate and collision angle were investigated. The aerosolisation performance was characterised with the size distribution of fragments and fine particle fraction (FPF) which was the mass fraction of the fragments with size less than 5 μm. The results showed that the collision between agglomerates has a significant effect on aerosolisation process. For a given agglomerate, there was a threshold velocity, above which would increase aerosolisation and otherwise would decrease. The analyses of airflow field and the agglomerate properties indicated that the aerosolisation performance was determined by two competitive factors, i.e. interparticle cohesion and total collision energy. An index to character of aerosolisation efficiency was provided based on the ratio of total collision energy and agglomerate strength. This index could be used to help design the high-dose DPI for the different drug agglomerates varied in strength. Highlights: The collision process included two stages: restructuring and fragmentation. FPF increased with airflow rate while sharply decreased with agglomerate strength. Increasing collision angle resulted in an increase of FPF and large fragments. Aerosolisation was determined by interparticle cohesion and collision energy. An index was provided to quantitatively characterize the aerosolisation efficiency.